English Competence Barriers among Publishing Students at Higher Education Institutions in Jakarta: Challenges and Implications for Academic and Professional Success - Putri, Liza Amalia; Clayton, Katherine (Jurnal Ilmiah Publipreneur, 2025)
This study investigates the barriers to English competence among publishing students at higher education institutions in Jakarta and explores the challenges these barriers pose for their academic and professional success. Despite the growing importance of English proficiency in the publishing industry and global academic communication, many students continue to struggle with language-related issues that hinder their learning outcomes and future career prospects. Through a mixed-method approach involving surveys and interviews with students and lecturers, the research identifies key obstacles such as limited exposure to English in daily academic contexts, lack of confidence in using English productively, and gaps in curriculum alignment with industry demands. The findings suggest that these barriers contribute to reduced engagement in English-based learning materials, limited participation in international publishing opportunities, and decreased competitiveness in the job market. The study concludes with recommendations for institutions to enhance English for Specific Purposes (ESP) instruction, integrate more authentic publishing-related English tasks, and foster an immersive language environment to better equip students for the global publishing landscape